Secular Difference in Body Mass Index From 2014 to 2020 in Chinese Older Adults: A Time-Series Cross-Sectional Study - Jiang, Ying; Zhang, Xiaomin; Xu, Tianwei; Hong, Weiqi; Chen, Zhiqi; Gao, Xiang; Xu, Renying (Frontiers in Nutrition, 2022)
Background: Body mass index (BMI) is the most widely used parameter to assess body weight status. Both the increase of BMI (overweight and obesity) and decrease of BMI (underweight) has associated high risk of adverse outcome, such as stroke, disability, and even death. However, recent data on secular differences in BMI in Chinese aged population is limited. The present study provides robust new evidence about the evolving epidemic of obesity among aged adults in China. Objective: Evaluating secular difference in BMI in a group of Chinese older adults. Materials and Methods: We analyzed 7 continuous survey years (2014-2020), including 50,192 Chinese aged participants (25,505 men and 24,687 women, aged 71.9±6.1 years, age range: 65-99 years). Information on sex, age, height, and body weight, was collected based on medical history. Participants were classified into four groups: underweight (BMI < 18.5 kg/m2), normal weight (18.5 kg/m2  BMI< 25 kg/m2), overweight (25 kg/m2  BMI< 30 kg/m2), and obesity (BMI 30 kg/m2). Linear regressions were used to assess the secular difference in BMI. Sex and age differences were also evaluated by stratified analyses. Results: From 2014 to 2020, age-adjusted mean BMI increased by 0.3 kg/m2 (95%CI: 0.1, 0.5 kg/m2) in men, and 0.5 kg/m2 (95%CI: 0.2, 0.7 kg/m2) in women. Age-standardized prevalence of underweight decreased from 3.0% to 2.3% in men, and from 3.0% to 2.1% in women. Age-standardized prevalence of overweight increased in both men (from 40.1% to 41.7%) and women (from 37.8% to 39.8%) and so as obesity (men: from 4.1% to 6.1%; women: from 5.8% to 8.7%). Conclusions: Our results confirmed that BMI gradually increased from 2014 to 2020. The age-adjusted mean BMI increased by 0.3 kg/m2 in older men, and 0.5 kg/m2 in older women. The age- and sex-standardized prevalence of overweight and obesity significantly increased, especially in 70-79-year age group, while the prevalence of underweight decreased. The combination of a balanced-diet and physical exercise is needed to maintain optimal BMI range for aged population.